2012
DOI: 10.3945/ajcn.111.022343
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acid load and risk of hypertension: the Rotterdam Study

Abstract: The findings from this prospective cohort study provided no evidence of an association between dietary acid load and risk of hypertension in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 32 publications
6
132
3
2
Order By: Relevance
“…To our knowledge, this is the first prospective study to evaluate the risk of type 2 diabetes associated with scores reflecting the acid load of the diet, such as PRAL or NEAP. In the Nurses' Health Study II, a high NEAP score was found to be associated with a higher risk of hypertension [11], while this was not confirmed in a recent study using both the PRAL and NEAP scores [3]. In the latter report, based on the Rotterdam Study with 2,241 participants, the multivariate HR comparing the third with the first PRAL tertile was 1.02.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…To our knowledge, this is the first prospective study to evaluate the risk of type 2 diabetes associated with scores reflecting the acid load of the diet, such as PRAL or NEAP. In the Nurses' Health Study II, a high NEAP score was found to be associated with a higher risk of hypertension [11], while this was not confirmed in a recent study using both the PRAL and NEAP scores [3]. In the latter report, based on the Rotterdam Study with 2,241 participants, the multivariate HR comparing the third with the first PRAL tertile was 1.02.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, type 2 diabetes incidence and glucose intolerance have been shown to be higher in people with a lower urinary pH than in those with a higher urinary pH [9]. Other studies that investigated the effect of an acid/base imbalance on health focused mainly on bone health, kidney stones [9,10] and hypertension; a positive association between hypertension and acid/base imbalance was reported in the Nurses' Health Study II [11], while a more recent prospective study in older Dutch adults from the Rotterdam Study failed to find any association [3].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, reducing the dietary acid load may offer one solution to improve health outcomes in patients with diabetes. Moreover, several cross-sectional and longitudinal studies have found a positive association between dietary acid load and increased risk for various chronic diseases, including diabetes, IR, nonalcoholic fatty liver, and cardiometabolic factors [8][9][10][11], but not hypertension [12].…”
Section: Introductionmentioning
confidence: 99%